NDIVIDUAL NEEDS OF SPOUSES WITH HIGH AND LOW LEVELS OF TRANSGRESSION - DAKOWICZ, ANDRZEJ (Studia Psychologica: Theoria et praxis, 2015)
One of the key elements of the Kozielecki’s theory of personality network is the motivation psychon. Its dynamics to the greatest extent depends on the strength of psychological needs. The aim of the research presented in the article was to determine the level of individual needs: vital, cognitive, social and personal, spouses with high and low levels of transgression. 100 couples were examined using the Scale of Transgression and the Test of Individual Needs. 30 spouses of high-level transgression and 30 spouses of low-level transgression were examined. There were no statistically significant differences in the intensity of the needs of mental strength between the wives with high and low level of transgression. Husbands with a high levels of transgression are characterized by much stronger cognitive needs than men with a low level of transgression, while men with a low level of transgression have a much stronger personal needs, than the men with a high level of transgression.